Development of fermented ice cream in combination with Lacticaseibacillus rhamnosus GG and persimmon puree and determination of physicochemical, rheological, textural and bioactive properties - Goktas, Hamza; Akhan, Senanur; Agan, Cansu; Bekiroglu, Hatice; Sagdic, Osman (UNIV ESTADUAL MARINGA, PRO-REITORIA PESQUISA POS-GRADUACAO, 2026)
This work aimed to produce six distinct ice creams: IC: control ice cream (without any probiotic or persimmon puree), ICP: ice cream with 20% persimmon puree, PIC: probiotic ice cream, FIC: fermented ice cream, ICFP: ice cream with 20% fermented persimmon puree, FICP: co-fermented ice cream with 20% persimmon puree. Lacticaseibacillus rhamnosus GG was used as the probiotic and fermentation agent. The addition of persimmon puree, probiotic inoculation and fermentation resulted in a reduction in the total dry matter content of the ice cream (P <= 0.05). Co-fermentation led to a notable reduction in the pH value, with the lowest pH observed in the FICP ice cream sample at 5.33 (P <= 0.05). The addition of persimmon puree resulted in a decrease in the L*values and an increase in both the a* and b* values of the ice cream samples. All ice cream samples exhibited pseudoplastic flow, and fermentation, persimmon puree addition and probiotic inoculation resulted in a reduction in K and hardness values. Co-fermentation had a protective effect on probiotic viability, with approximately 8.95 +/- 0.01 log CFU g(-1) of probiotic viability detected in the FICP ice cream sample after 120 days of storage. Furthermore, co-fermentation markedly enhanced the bioactive characteristics of the samples, with the FICP sample exhibiting the highest TPC, CUPRAC, and DPPH values (242.57 +/- 11.52mg GAE 100g(-1), 22.95 +/- 0.29mg TE 100g(-1), and 48.02 +/- 3.27%, respectively). The study demonstrated that persimmon can be employed in the production of ice cream, with the co-fermentation of the ice cream mix promoting the viability of probiotics and enhancing the bioactive characteristics of the ice cream samples.
Keywords: Fermented ice cream; probiotic; L. rhamnosus; persimmon puree; probiotic viability; antioxidant activity; STORAGE; HEALTH; Science & Technology - Other Topics